Hospital Morbimortality from Chronic Sinusitis in Brazil, from 2016 to 2020 (Research, Society and Development, 2022)
Sinusitis is characterized by inflammation of the paranasal sinuses, cavities lined by mucus-secreting mucosa and covered with cilia, located in the skull, susceptible to inflammation in the presence of allergic, anatomical and environmental changes. It can be acute or chronic, both with the same symptoms. Although it is a relatively easy disease to manage, there are cases of hospitalization for this pathology and its epidemiological study is infrequent. The objective of this study was to study hospital morbidity and mortality from chronic sinusitis in Brazil from 2016 to 2020. An epidemiological study of a time series was carried out, addressing hospitalizations and deaths from hospitalizations in Brazil, with data from the SUS Hospital Information System (SIH/SUS ), which were tabulated in Excel and statistically analyzed in the Bioestat 5.3 program, whose results were presented in graphs, tables and expressed in absolute numbers, frequencies and descriptive statistics (mean, standard deviation and coefficient of variation). The results found showed that there were 12,897 hospitalizations for chronic sinusitis in the study period, with an increasing trend until 2019 and a decrease in 2020. The regions with the highest frequency were the Southeast and South, the age group was 50 to 59 years and the white race . The total cost was R$8,841,668.77, with 39 hospital deaths. Faced with a disease with many treatment possibilities, the presence of deaths in hospitalized patients is worrying. It is assumed, therefore, that there should be improvements in care, even in Primary Care, with improvements in treatment, avoiding chronification, as well as the unfolding in hospitalizations and subsequent deaths.